The Role of Students as Agents of Change Towards Climate Change Action for SDGs - Ghafur, Fadolul; Alviansyah, Riezky (IAIN Madura, 2025)
The increase in air temperature is one of the indicators that climate change has occurred in Indonesia, according to the historical air temperature data of the Meteorology, Climatology and Geophysics Agency (BMKG) from 1981-2018. The data shows an increase of around 0.03°C each year. Actions that can be taken related to climate change by involving the entire community to increase awareness of the environment. One of the ways to take action on climate change is through agents of change. Agents of change must have critical thinking and solution on every impact that causes damage and loss. This research uses qualitative methods and primary data collection with Focus Group Discussions (FGD), observations and secondary data with literature studies. The use of the STEM or Science, Technology, Engineering and Mathematics approach is carried out indoor and outdoor to foster the ability of students as agents of change. Students as agents of change will carry out several strategies in climate change action which includes the 13th goal in the Sustainable Development Goals. Activities that can be done by forming FGD to examine the problems that are being faced and how they will affect the future for students.